Financial Inclusion as Mediator in the Relationship of Social Capital and Financial Literacy Towards Business Performance - Mimelientesa Irman; Budiyanto Budiyanto; Suwitho Suwitho (Universitas Negeri Malang, 2022)
This study examines the performance problems of SMEs in the trade sector in Pekanbaru by using several internal company factors to build a competitive strategy. The study involved 300 SMEs consisting of 26 wholesalers and 274 retailers in Pekanbaru, Riau. This research adopted a structural equation model (SEM) approach with AMOS for hypothesis testing. The results indicate that social capital and financial literacy have a significant direct effect on the performance of the SMEs businesses in the trade sector in Pekanbaru. It implicates that social capital and financial literacy are two determining factors for the success of SMEs businesses. However, social capital does not affect business performance indirectly through the role of financial inclusion. Meanwhile, financial literacy in this study, directly or indirectly, through financial inclusion can improve the performance of SMEs businesses. This study shows that SMEs in the trade sector in Pekanbaru must continue to foster partnerships with existing associations, and they also need to be directed so as not to deviate from the common goal of advancing the SMEs businesses. Keywords: Financial Literacy, Financial Inclusion, SMEs’ Business Performance, Social Capital